Verotoxin-1 Induces Tissue Factor Expression in Human Umbilical Vein Endothelial Cells through Activation of NF-κB/Rel and AP-1 - Ishii, Hidemi; Takada, Kimihiko; Higuchi, Toshiyuki; Sugiyama, Junichi (Thrombosis and Haemostasis, 2000)
This study examined the effect of verotoxin-1 (VT-1), which is released from Escherichia coli O157:H7, on endothelial expression of tissue factor (TF), a cofactor required to initiate blood coagulation. In order to elucidate the molecular basis for development of hemolytic uremic syndrome (HUS) in patients infected with E. coli O157:H7, human umbilical vein endothelial cells (HUVECs) were exposed to purified VT-1. VT-1 increased both TF activity and TF mRNA in HUVECs without loss of cell viability in a time-and dose-dependent manner from 0.1 to 10 ng/ml VT-1. Nuclear proteins extracted from VT-1-stimulated HUVECs bound to the consensus NF-κB/Rel and AP-1 binding oligonucleotides in a dose-dependent manner within 2 h after the stimulation in electrophoretic mobility shift assays (EMSA). Nuclear proteins from VT-1-stimulated HUVECs formed two complexes with the NF-κB/Rel binding motif in the human TF promoter (TF-κB motif). The supershift assays, using antibodies for human p65, p50 or c-Rel, indicated that the lower complex was composed of p65/p50 and the higher complex was a p65 homo-or hetero-dimer with the Rel family, except c-Rel. The human TF promoter contains two AP-1 binding sites, the proximal and distal AP-1 binding sites. The supershift assays indicated that AP-1 containing mainly c-Jun and JunD, positively bound to the proximal AP-1 motif of TF (TF-AP-1). The distal TF-AP-1 motif did not show positive binding with nuclear proteins from VT-1-stimulated HUVECs. Pretreatment of HUVECs with curcumin, an inhibitor of NF-κB/Rel activation, synthesis of c-Jun mRNA and binding of activated AP-1 with AP-binding oligonucleotide, prevented the VT-1 induced increase in TF mRNA and activity in VT-1-stimulated HUVECs. Curcumin also inhibited NF-κB and AP-1 binding to TF-κB and proximal TF-AP-1 oligonucleotides, respectively, in a dose-dependent manner. The present work suggests that both the NF-κB/Rel and AP-1 activated in endothelial cells by stimulation with VT-1 binds to the TF-κB and proximal AP-1 binding sites, respectively, of the TF promoter.
Keywords: Endothelial cells; tissue factor; Escherichia coli O157; verotoxin